Histopathological evaluation of Ankaferd blood stopper use in the rabbit septoplasty model - Orhan, İsrafil; Do?an, Remzi; Soylu, Erkan; Aksoy, Fadlullah; Veyseller, Bayram; Özturan, Orhan; Eşrefo?lu, Mukaddes; Aydın, Mehmet Şerif (Elsevier Ireland, 2015)
Objective: The purpose of this study was to assess the use of Ankaferd blood stopper (ABS), an organic hemostatic agent of plant origin, in septoplasty operations, and to determine its effect on nasal septal tissues in the rabbit model. Method: The study was performed on 30 New Zealand adult male rabbits each weighing 2500-3500 g (average: 3000 g). The rabbits were randomly divided into 4 groups, namely, the control group (without septoplasty), the septoplasty + tampon group, the septoplasty + ABS group, and the septoplasty + tampon + ABS group. All animals were sacrificed after two weeks, and the nasal septums were total removed using the lateral rhinotomy technique. The specimens were obtained from similar sites of cartilaginous nasal septum. The sections were stained with hematoxylin-eosin and Mason trichrome stains and studied under the light microscope by the same pathologist who evaluated the mucosal ulcerations, the severity of inflammatory cell infiltration, the mucosal thickness, and the cartilage thickness. The data obtained were statistically analyzed using the Kruskal-Wallis variance analysis and the Mann-Whitney U test. Results: No mucosal ulceration or inflammatory cell infiltration was detected in any of the rabbit groups. There was a statistically significant difference between the groups in terms of mucosal thickness and cartilage thickness (p < 0.05). The values of mucosal thickness in the groups mentioned above were 147.7 +/- 17.6 mu m, 205.7 +/- 36.7 mu m, 139.6 +/- 14.8 mu m, and 190.2 +/- 17.5 mu m, respectively. The values of cartilage thickness were 398.2 +/- 28.9 mu m, 546.2 +/- 35.3 mu m, 363.7 +/- 24.7 mu m, and 447.8 +/- 28.2 mu m, respectively. There was no significant difference between the control group and the septoplasty + ABS group in terms of mucosal thickness and cartilage thickness (p > 0.05). However, there was a significant increase in nasal mucosal and cartilage thickness in tampon-using groups when compared with the other groups (p < 0.05). Conclusion: Although nasal tampons provide the contact of mucoperichondrium with the cartilage, they are generally accepted as a discomfort for patients. Ankaferd blood stopper can be used instead of nasal tampons to increase patient comfort.
WOS: 000350183800005
PubMed ID: 25596649
Keywords: Rabbit; Ankaferd Blood Stopper; Septoplasty